0
$\begingroup$

I am required to show that all partial order derivatives of the function $f:\mathbb{R}^2\rightarrow \mathbb{R}$ defined by

$$ f(x,y) = \begin{cases} \dfrac{xy(x^2-y^3)}{x^3+y^3} & \text{if } (x,y) \neq (0,0) \\ 0 & \text{if } (x,y) = (0,0) \end{cases} $$

exists everywhere, but the mixed second order partial derivatives are unequal at the $(0,0).$

I tried to solve it as follows:
find $D_{11}$, $D_{12}$, $D_{21}$ and $D_{22}$ of the function, and thereafter try to show that at $D_{12}(0,0) \neq D_{21}(0,0).$

With some tedious calculations $$ D_{12} = \frac{x^6+9x^4y^2-9x^2y^4-y^6}{(x^2+y^2)^3} \\ D_{21} = \frac{9x^4y^2-y^6-9y^4x^2+x^6}{(x^2+y^2)^3} $$

My doubts are:

  1. At $(0,0)$ both $D_{12}$ and $D_{21}$ work out to $0$ only so I am going wrong somewhere.

  2. I am getting confused with initial condition $f(x,y) = 0$ if $(x,y) = (0,0).$ Because if $(x,y)=(0,0)$ and we need to show inequality at $(0,0)$, isn't the function $0$ and hence both $D_{12}$ and $D_{21}$, therefore $0$, $0$?

  3. Is there any good textbook/link on web where I can get more practice problems similar to this?

Request guide to understand the problem

$\endgroup$
  • $\begingroup$ I did see an almost similar question for first order partial derivative on this forum... but I have still not understood it $\endgroup$ – SAK Nov 5 '16 at 18:13
0
$\begingroup$

First, $f$ is a quotient of polynomials with no singularities except at $(0,0)$, so it is smooth everywhere except at $(0,0)$.

Second, this only makes sense if you use the (more) "real" definition of the derivative, using limits, i.e: $$ \partial_x g(x,y)|_{a,b} = \lim_{h\rightarrow 0} (g(a+h,b) - g(a,b))/h $$ Note that your expressions are, literally, identical: $D_{12}=D_{21}$, so you would need some other information to see they are not the same.

We are looking at: $$ f(x,y) = \frac{xy(x^2-y^3)}{x^3 + y^3} $$

Here, just use the definition starting from the first derivatives: $$ f_x=\partial_x f = \frac{ x^2(3+2x)y^4 - y^7 }{(x^3 + y^3)^2} \;\;\;\;\&\;\;\;\; f_y=\partial_y f = \frac{x^6 - 2x^3(1+2x)y^3 - xy^6}{(x^3 + y^3)^2} $$ Then, we can do: \begin{align} \partial_{x}f_y|_{0,0} &= \lim_{h\rightarrow 0} (f_y(0+h,0) - f_y(0,0))/h \\ &= \lim_{h\rightarrow 0} f_y(h,0)/h \\ &= \lim_{h\rightarrow 0} \frac{h^6}{h^6}\frac{1}{h} \\ &= \infty \end{align} \begin{align} \partial_{y}f_x|_{0,0} &= \lim_{h\rightarrow 0} (f_x(0,0+h) - f_x(0,0))/h \\ &= \lim_{h\rightarrow 0} f_x(0,h)/h \\ &= \lim_{h\rightarrow 0} \frac{ -h^7 }{h^6} \\ &= 0 \end{align} which shows that $\partial_{xy}f(0,0)\ne\partial_{yx}f(0,0)$. Hopefully I didn't make any mistakes!

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.